2020
DOI: 10.1111/ijcs.12600
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception of packaging: An eye‐tracking study of gluten‐free cookies

Abstract: The growing interest in gluten‐free products makes it crucial to understand the mechanism of consumers' perception of gluten‐free claims. Due to the limited research measuring the influence of the type (verbal/nonverbal), number and location of gluten‐free statements on product labels on visual attention and consumers' purchase decisions, the main aim of this research was to evaluate the perception of gluten‐free claims and the Crossed Grain symbol on cookie packages of both consumers who are on a gluten‐free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(75 reference statements)
0
27
1
Order By: Relevance
“…In Poland, an eye-tracking study of gluten-free cookies showed that consumers were more uncertain about the crossed grain symbol, as compared to verbal statements and gluten-free claims. 23 In contrast, about half of our sampled population agreed that "sugar-free"-labeled products are artificially sweetened. However, they had little idea about the artificial additives which act as sugar substitutes: 75.6% of the overall responders were not familiar with the role of xylitol, sorbitol, and aspartame sweeteners.…”
Section: Discussionmentioning
confidence: 80%
“…In Poland, an eye-tracking study of gluten-free cookies showed that consumers were more uncertain about the crossed grain symbol, as compared to verbal statements and gluten-free claims. 23 In contrast, about half of our sampled population agreed that "sugar-free"-labeled products are artificially sweetened. However, they had little idea about the artificial additives which act as sugar substitutes: 75.6% of the overall responders were not familiar with the role of xylitol, sorbitol, and aspartame sweeteners.…”
Section: Discussionmentioning
confidence: 80%
“…In today's world, eye tracking can be found in many fields. This includes human-machine interaction [60,1], computer graphics [84,70], self-diagnosis systems [62,81,65], measurement of eye misalignment [71,15], detection of neurological diseases [10,74], behavioral research [66,7], learning systems [73,61], expertise determination [5,77], driver observation [67,78,24], market research [4,79], and many more.…”
Section: Introductionmentioning
confidence: 99%
“…One problem that exists here is the need for many scan paths, which is necessary for testing the system. In the area of market research, one evaluates product placements or the online presence of manufacturers and sellers [4,79]. Here, many scan paths are also needed to make a general statement or a statement about specific customer groups.…”
Section: Introductionmentioning
confidence: 99%
“…(Wu, 1999;Gao & Gudykunst, 1990;Buhr & Dugas, 2002). Therefore, in order to increase transaction success rates, merchants often provide more information through product packaging, labeling and even virtual reality (VR) technology to eliminate uncertainty concerns for users and investors (Kostis & Ritala, 2020;Sielicka-Różyńska et al, 2020;Lye et al, 2020). However, in the 21st century, a growing number of researchers have found that uncertainty stimuli exhibit unexpectedly positive effects, especially when applied them to commercial activities (Ruan et al, 2018;Shen et al, 2018;Hill et al, 2016;Sevilla & Meyer, 2020;Guo et al, 2019;Moon & Nelson, 2019).…”
Section: Introductionmentioning
confidence: 99%